International Congress on Applications of Lasers &Amp; Electro-Optics 2005
DOI: 10.2351/1.5060477
|View full text |Cite
|
Sign up to set email alerts
|

Sensor integration for robotic laser welding processes

Abstract: The use of robotic laser welding is increasing among industrial applications, because of its ability to weld objects in three dimensions. Robotic laser welding involves three sub-processes: seam detection and tracking, welding process control, and weld seam inspection. Usually, for each sub-process, a separate sensory system is required. The use of separate sensory systems leads to heavy and bulky tools, in contrast to compact and light sensory systems that are needed to reach sufficient accuracy and accessibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…In [3] and [4], laser-stripe sensors are developed. In [5], three laser-stripes are used to detect the seam more effectively. For the welding purpose, there are several commercial devices [6].…”
Section: Introductionmentioning
confidence: 99%
“…In [3] and [4], laser-stripe sensors are developed. In [5], three laser-stripes are used to detect the seam more effectively. For the welding purpose, there are several commercial devices [6].…”
Section: Introductionmentioning
confidence: 99%
“…Laser structured light is usually used to extract and track the weld contour in the form of laser emitter and monocular camera. There are a variety of shapes of the laser stripe, including linear [23], multi-linear [24], a cross [25], a triangle [26], etc. SHAO [24] designed three different wavelengths of laser to measure the seam width, seam center, and the normal vector of the weld face, and the result of experiment revealed that the proposed method could meet the precision demand of space narrow butt joint.…”
mentioning
confidence: 99%